Research in finance. Volume 27 - Kensinger, John W. (Research in finance,, 2011)
The theme of this volume is Recovering from Financial Crisis. The lead chapter sets the theme by giving insight into the recent surge in going-private transactions (and the corresponding reduction of Initial Public Offerings). The author develops evidence (reaching back 25 years) that going-private transactions tend to be inversely related with the return on diversified equity portfolios, suggesting that the recent upswing in going-private transactions in the United States is not simply the result of the Sarbanes Oxley Act of 2002. The second chapter offers insights into the recent round of hedge fund failures. Then, the third chapter offers new insights into some of the more controversial aspects of private equity arrangementswhen private equity arrangements are expressed as real options, the actions of the managing partners are more readily understandable. The fourth chapter offers insights into why commodity producers (such as oil companies) choose not to hedge, so that their stock can offer shareholders the opportunity to gain valuable diversification benefits using the stock as a pure play in the commodity. Remaining chapters offer further insights into recent trends in IPO activity, lease versus purchase decisions, agency costs, project risk, and emerging markets.